Monitoring and Evaluation of Ecological Environment Changes in Dongzhuang Reservoir Basin in Shaanxi Province Based on Remote Sensing Ecological Index - Quan Wenting; Zhang Shuyu; Liu Yan; Wang Weidong (Shuitu baochi tongbao)
[Objective] Real-time and accurate monitoring of the ecological environment of the Dongzhuang reservoir basin in Shaanxi Province was carried out to provide data and theoretical support for the development and protection of the watershed and urban economic development. [Methods] Landsat remote sensing images in 2000, 2010, and 2020 were selected, and four indexes (humidity, greenness, dryness, and heat) were constructed based on the Google Earth Gngine (GEE) platform. The remote sensing ecological index (RSEI) was calculated by the principal component analysis method, and the ecological environment changes in the Dongzhuang reservoir basin over the past 20 years were monitored and evaluated. The CA-Markov model based on IDRISI software was used to simulate the ecological environment of the Dongzhuang reservoir basin in 2030. [Results] ① During the past 20 years, the ecological environment of the Dongzhuang reservoir basin has been maintained at the same level, and average RSEI increased from 0.499 to 0.500, indicating a slight increase in the ecological environment. ② According to changes in RSEI values, the ecological environment of the Dongzhuang reservoir basin over the past 20 years was relatively complex, and both improvement and deterioration of the ecological environment continued to coexist for a long time. The policy of returning farmland to forest instituted in 1999 in the Weibei region played a positive role in the improvement of the ecological environment, and its effect has begun to be prominent. [Conclusion] The ecological environment of the Dongzhuang reservoir basin has deteriorated mainly in the towns and their surrounding areas, while the improved areas have mainly occurred in the forest and hilly areas. It is still necessary to give more attention to the balance between rapid economic development and ecological environment management.